Food Safety in EU Higher Education - Bánáti, Diána (Acta Agraria Debreceniensis, 2007)
Under the aegis of the Lisbon Strategy, special attention is paid to education and areas left untouched by the European integration process. Human capital and research inputs were identified as major driving forces for long-term development. The European Union is keen on meeting its target of boosting research spending to 3% of GDP by 2010. In order to contribute towards his goal, the European Commission has set aside an amountwhich is double the budget of the 7th Framework Programme. Accordingly, preferences were given to research and development projects encouraging competitiveness in the food industry and other initiatives, such as the European Technology Platforms. Major obstacles to innovation in Hungary are: lack of funds, weakness of research network, poor structural relations. Better utilization of our comparative advantages should be targeted in order to have the Hungarian food industry become a driving force sector. This is to be promoted by the newly transformed foodengineer training (as a result of the Bologna Declaration) which can adapt better to the changing requirements of the labour market. Food science and related research could become determining factors for the food economy by setting up accredited training systems and enhancing food safety education and training in Hungary.